Improvement of Psychological Health Aspect of Tuberculosis Client Through Psychoeducation - Nisa, Nurul Khoirun (Babali Publisher, 2020)
Introduction: Tuberculosis is well known as an infectious disease on lungs system caused by Mycobacterium tuberculosis in physical, social and mental health conditions. Methods: This research applied quasi-experiment and consisted of pre and post-test on non-equivalent control group. The subjects were divided into two groups, control group (35) and treatment group (35) by using simple random sampling technique based on inclusion criteria. The research was conducted at Health Center, Jombang. The variables involved in this research were psycho-education psychological aspects. Results: The results of the research showed that physical and psychological aspects on both treatment and control groups is with p = 0.000 (<0.05) which means that there is significant difference on psychological aspect between treatment and control groups. Psycho-education significantly influenced psychological among the patients with tuberculosis. Conclusion: This change occurred due to the increase of health on the patient with tuberculosis in psychological aspects and also it followed by the decrease of symptoms on the patient.